Time- and dose-dependency of radiographic normal tissue changes of the lung after stereotactic radiotherapy - Hof, Holger; Zgoda, Jacqueline Sandra; Nill, Simeon; Höss, Angelika; Kopp-Schneider, Annette; Herfarth, Klaus; Debus, Jürgen; Plathow, Christian (International journal of radiation oncology, biology, physics, 2010)
Purpose - Normal tissue changes (NTC) of the normal lung parenchyma are commonly seen after stereotactic single-dose radiotherapy (radiosurgery) of lung tumors. The aim of this study was to investigate the extent and dynamics of NTCs after radiosurgery. - Methods and Materials - Fifty lung tumors in 49 patients were treated with radiosurgery. Follow-up CTs were anatomically matched to the treatment planning CTs, incorporating the treatment plan and enabling spatial correlation of initial radiation dose distribution and subsequent NTCs of the lung. Lung parenchyma was divided into nine areas of different radiation dose exposures (range, 6-35 Gy). Areas were investigated and compared at different time points according to the development of NTCs. - Results - Twenty-six patients developed NTCs during follow-up. The evaluation of the dependency of the extent of NTCs on the amount of radiation dose lead to a linear model for the fixed effects: Fraction of reacting volume = InterceptT + 0.0208 ∗ Dose (“Dose” should be given in Gy). Dose had a slope of 0.0208 (fraction of normal tissue reaction/Gy) (SE 0.000804, p < 0.0001), implying a significant correlation between dose level and the extent of NTC. - Conclusion - For radiosurgery of lung tumors, a significant correlation of radiation dose and the extent of NTCs could be demonstrated. Using the introduced formula, a preview on the extent of NTCs to develop in normal lung parenchyma according to the dose level can be performed.